Fatigue crack growth in micro specimens as a tool to measure crack–microstructure interactions. Issue 12 (25th October 2020) - Grünewald, Patrick; Rauber, Jonas; Marx, Michael; Motz, Christian; Schaefer, Florian
Abstract: The process of short fatigue crack growth plays a significant role for the lifetime of materials in the high and very high cycle regimes. Fatigue crack growth is strongly influenced by interactions with microstructural obstacles, such as grain boundaries or phase boundaries, requiring a better understanding of these interactions to enhance the lifetime in these load regimes and improve lifetime calculations. Although it is possible to obtain crack growth rates from fatigue cracks in the lower micrometre range, further information like the exact position and type of the obstacle are mostly unavailable during the experiment. To overcome this issue, we propose a testing methodology of fatigue crack growth in micro specimens, which allows for an exact positioning of the crack relative to the obstacles and for monitoring the crack behaviour in a scanning electron microscope. The capabilities of this method are demonstrated for the interaction of fatigue cracks with grain boundaries.